A combined chemical and enzymatic method to determine quantitatively the polysaccharide components in the cell wall of yeasts. Issue 6 (28th July 2014) - Schiavone, Marion; Vax, Amélie; Formosa, Cécile; Martin‐Yken, Hélène; Dague, Etienne; François, Jean M.
Abstract A reliable method to determine cell wall polysaccharides composition in yeast is presented, which combines acid and enzymatic hydrolysis. Sulphuric acid treatment is used to determine mannans, whereas specific hydrolytic enzymes are employed in a two sequential steps to quantify chitin and the proportion of β‐(1, 3) and β‐(1, 6)‐glucan in the total β‐glucan of the cell wall. In the first step, chitin and β‐(1, 3)‐glucan were hydrolysed into their corresponding monomers N‐acetylglucosamine and glucose, respectively, by the combined action of a chitinase from Streptomyces griseus and a pure preparation of endo/exo‐β‐(1, 3)‐glucanase from Trichoderma species. This step was followed by addition of recombinant endo‐β‐(1, 6)‐glucanase from Trichoderma harzianum with β‐glucosidase from Aspergillus niger to hydrolyse the remaining β‐glucan. This latter component corresponded to a highly branched β‐(1, 6)‐glucan that contained about 75–80% of linear β‐(1, 6)‐glucose linked units as deduced from periodate oxidation. We validated this novel method by showing that the content of β‐(1, 3), β‐(1, 6)‐glucan or chitin was dramatically decreased in yeast mutants defective in the biosynthesis of these cell wall components. Moreover, we found that heat shock at 42 °C in Saccharomyces cerevisiae and treatment of this yeast species and Candida albicans with the antifungal drug caspofungin resulted in 2‐ to 3‐fold increase of chitin and in a reduction of β‐(1, 3)‐glucan accompanied by an increase of β‐(1, 6)‐glucan, whereas ethanol stress had apparently no effect on yeast cell wall composition.